Isolated Tillaux fracture in an adult: a rare case and review of management - Pandey, Arun; Meena, Anil; Mall, Suhas Kumar; Vempalli, Nagasubramanyam; Kumar, Arvind; Singh, Shashi; Sireesha, Konda (International Journal of Research in Orthopaedics, 2026)
Isolated Tillaux fractures of the ankle joint are predominantly seen in adolescents due to the presence of open epiphyses, which makes the region more susceptible to injuries. In adults, this fracture is rare because the anterior inferior tibiofibular ligament (AITFL) typically ruptures before bone avulsion occurs. These injuries can be easily missed or misdiagnosed. Recognizing such injuries is critical to prevent long-term complications, including joint instability and post-traumatic arthritis. We report a rare case of an isolated Tillaux fracture in a 35-year-old male following a road traffic accident. This report outlines our diagnostic approach, management strategy, and postoperative outcome.